Peningkatan Kemandirian Ekonomi PPDI Balikpapan Melalui Penguatan Branding Google Sites dan Pemberdayaan Legalitas Produk - Alif, Muhammad Ikhsan; Septyanto, Arif Wicaksono; Sartika, Widya; Anugrah, Bisma Mukti; Malika, Nadya Siti; Sitompul, Sophie Theodore; Efendi, Naura Alya Priskila; Hidayah, Aqilla Rahma; Hendriani, Andini Callista; Hermawan, Adhitya (Abdimas Universal, 2026)
The Indonesian Persons with Disabilities Association (PPDI) often faces social, economic and technological barriers, especially in developing Micro, Small and Medium Enterprises (MSMEs). In the digital era, low digital literacy, visual quality of products, and understanding of business legality are obstacles in marketing. PPDI Balikpapan as an organization of people with disabilities has great potential in economic empowerment, but needs strategic support in digital promotion. This service activity is carried out to improve the competitiveness of MSMEs with disabilities through product photo documentation, website creation with Google Sites, and training on business licensing / Business Identification Number (NIB) through OSS, honey halal certification assistance training. The methods used are direct assistance, technical practice, and adaptive training. The results showed an increase in product visual quality, the presence of an easily accessible online catalog, and participants' understanding of the importance of business legality (NIB and halal certification). This activity is proven to be able to strengthen branding and expand the market reach of MSMEs with disabilities in an inclusive and sustainable manner.